Upaya Meningkatkan Hasil Belajar Passing Bawah Bolavoli dengan Menggunakan Gaya Mengajar Inklusi pada Siswa Kelas V Mi Darul Huda Tahun Ajaran 2022/2023 - Rohman, Ahmad Fathur; Muharram, Nur Ahmad; Junaidi, Slamet (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The purpose of this study was to improve the learning outcomes of volleyball underhand passing by applying the inclusive teaching style to Class V students of MI Darul Huda Academic Year 2022/2023. This research is a Classroom Action Research (CAR). This research was conducted in two cycles, consisting of four stages in each cycle consisting of planning, action, observation, and reflection. The research subjects were Class V students of MI Darul Huda Academic Year 2022/2023, totaling 26 students consisting of 15 male students and 11 female students. Data collection techniques with tests and observations. Data validity uses data triangulation techniques. Data analysis used descriptive qualitative with percentage techniques. The results of data analysis in cycle I obtained learning outcomes of 26 students (100%) achieving complete criteria in the cognitive aspect, psychomotor aspects of 14 students (28%) achieving complete criteria in volleyball underpassing, while in the affective aspect 1 student ( 4%) got the Very Good category (A), 23 students (88%) got the Good category (B), and 2 students (8%) got the Enough category (C). In cycle II, the learning outcomes were obtained by 26 students (100%) achieving the complete criteria in the cognitive aspect, the psychomotor aspect of 24 students (92%) achieving the completion criteria in volleyball underpassing, while in the affective aspect of 3 students (12%) ) got the Very Good category (A), and 23 students (88%) got the Good category (B). Based on the results of this study, it was concluded that applying an inclusive teaching style can improve learning outcomes of volleyball underhand passing in Class V MI Darul Huda Academic Year 2022/2023. Keywords: Learning Outcomes, Underpassing, Volleyball, Teaching Style Inclusion